2006
DOI: 10.1017/s0012162206000454
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial problems and seizure-related factors in children with epilepsy

Abstract: In this study we describe psychosocial functions and seizurerelated factors in a population-based sample of children with epilepsy. Psychosocial problems (Achenbach scales), cognitive function, and socioeconomic status were studied in 117 children with epilepsy aged between 6 and 13 years (mean age 11y [SD 2y 1mo] and 10y 8mo [SD 2y]; 71 males, 46 females) and in randomly selected controls matched with 117 children for sex and age (mean age 11y 2mo [SD 2y 1mo] and 10y 5mo [SD 2y 4mo]; 69 males, 48 females). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 21 publications
7
50
0
Order By: Relevance
“…The classical community-based Isle of Wight study demonstrated higher rates of behavioral problems in children with uncomplicated epilepsy (29%) than children with other chronic non-neurological conditions (12%), and those in the general population (7%) [1,2]. This is in accordance with recent community based studies from Britain [3] and Norway [4,5]. An even higher prevalence, 21%-60%, is found as one moves from community-based samples to hospital-based cohorts [6][7][8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The classical community-based Isle of Wight study demonstrated higher rates of behavioral problems in children with uncomplicated epilepsy (29%) than children with other chronic non-neurological conditions (12%), and those in the general population (7%) [1,2]. This is in accordance with recent community based studies from Britain [3] and Norway [4,5]. An even higher prevalence, 21%-60%, is found as one moves from community-based samples to hospital-based cohorts [6][7][8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 83%
“…However, different informants' ratings of problem behavior in children with somatic diseases may be different from those of healthy children. In a population based study of children with epilepsy, mothers and teachers reported increased problem rates compared to controls, while the adolescents themselves did not [5].…”
Section: Introductionmentioning
confidence: 92%
“…A study conducted in an outpatient clinic for children and adolescents with obstructive sleep disorders (Uema, Vidal, Fujita, Moreira, & Pignatari, 2006) reported that one quarter presented externalizing disorders. Children and adolescents with epilepsy presented more behavioral and emotional problems than the control group, especially the boys (Høie et al, 2006). Zashikhina and Hagglof (2007) found similar results when studying adolescents with chronic diseases, especially girls with asthma and boys with epilepsy.…”
supporting
confidence: 51%
“…The risk for psychiatric disorders in people with epilepsy have been reported to be three to six times higher than observed in age matched apparently healthy population [1,15,18]. It has also been documented that children and adolescents with epilepsy experience more emotional and behavioural problems than healthy controls and others with chronic conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Both epilepsy and depression are characterized by a chronic course and poor long-term psychosocial outcome [2]. Authors have identified psychiatric syndromes such as anxiety, depression, and behavioural affective and conversion disorders in people with epilepsy [8][9][10][11][12][13][14][15][16][17][18]. The risk for psychiatric disorders in people with epilepsy have been reported to be three to six times higher than observed in age matched apparently healthy population [1,15,18].…”
Section: Introductionmentioning
confidence: 99%